HUBUNGAN KREATIVITAS, KEDISIPLINAN PESERTA DIDIK DAN KELENGKAPAN SARANA PRASARANA SEKOLAH DENGAN HASIL BELAJAR FISIKA PESERTA DIDIK - Hasniati; Rafiqah; Andi Dian Angriani (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to determine the description of students' creativity, student discipline, completeness of school infrastructure and the relationship between student creativity, student discipline and completeness of school infrastructure together with physics learning outcomes of students in class XI MIPA SMAN throughout the Regency. Jeneponto. This type of research is a correlation or relationship research that is Ex Post Facto. The research population is 14 schools. The sample in this study was Class XI MIPA students from 4 schools with cluster random sampling technique. Data was collected by means of questionnaires, interviews, observation sheets and documentation. The results of this study indicate that there is a positive relationship between students' creativity, student discipline and the completeness of school infrastructure together with the physics learning outcomes of students in class XI MIPA SMAN throughout Jeneponto Regency.